RISK PROFILE, GOOD CORPORATE GOVERNANCE AND CAPITAL ON PROFIT GROWTH IN ISLAMIC COMMERCIAL BANKS - Asrah, Asrah (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2025)
This study aims to analyze the effect of Risk Profile, Good Corporate Governance, and Capital on Profit Growth in Islamic Commercial Banks. These three independent variables are part of the bank soundness assessment approach known as the RGEC method. However, in this study, the Earning variable is excluded to avoid duplication of indicators directly related to profit. The Risk Profile is measured using the Non-Performing Financing (NPF) ratio, Good Corporate Governance is measured through the Operational Expenses to Operating Income (BOPO) ratio, and Capital is measured using the Capital Adequacy Ratio (CAR). Meanwhile, profit growth is measured based on the percentage increase in current year profit. This study uses a quantitative approach with a descriptive-associative method. The research population consists of all Islamic Commercial Banks registered with the Financial Services Authority (OJK) during the 2019–2023 period, from which a sample of 10 banks was obtained using purposive sampling. The data used are secondary data sourced from annual financial reports and bank GCG reports obtained through the official websites of the Financial Services Authority and each bank. The data analysis techniques include classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination using IBM SPSS 26. The results show that partially, the Risk Profile variable has a positive and significant effect on profit growth, while Good Corporate Governance and Capital have a positive but insignificant effect. Simultaneously, the three variables have a positive and significant effect on profit growth. The limitations of this study lie in the exclusion of the Earning variable as part of the complete RGEC approach, as well as the data coverage being limited to only 10 banks and a five-year period. Future research is expected to include other variables and expand the number of samples and observation periods to obtain more comprehensive and generalizable results.